2009
DOI: 10.1021/ja901649s
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Controlled Access to [4 + 2] and [4 + 3] Cycloadditions in Gold-Catalyzed Reactions of Allene-Dienes

Abstract: By adjusting the electronic properties of the ancilliary ligands high selectivity can be achieved for either gold(I)-catalyzed [4+2]- or [4+3]-cycloaddition reactions of diene-allenes. Triarylphosphitegold(I) complexes are employed as catalysts for a [4+2]-cycloaddition reactions leading to alkylidenecyclohexenes. Conversely, di-t-butylbiphenylphosphinegold(I)-catalyzed reactions afford cycloheptadienes via [4+3]-cycloaddition reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
96
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(102 citation statements)
references
References 35 publications
(27 reference statements)
2
96
1
Order By: Relevance
“…[6,7] Therefore, we became interested in the behaviour of furan derivatives in the presence of allenyl ethers and cationic gold(I) catalyst A. Allenyl ether 1b was allowed to react with furan under our standard reaction conditions which furnished a Mukaiyama-Micheal type 1,4-addition product 6a in 38% yield. The treatment of 2-methylfuran did not alter the reaction pattern, and 1,4-addition product 6b was obtained in a better yield (59%).…”
Section: Entries 2-5)mentioning
confidence: 99%
See 1 more Smart Citation
“…[6,7] Therefore, we became interested in the behaviour of furan derivatives in the presence of allenyl ethers and cationic gold(I) catalyst A. Allenyl ether 1b was allowed to react with furan under our standard reaction conditions which furnished a Mukaiyama-Micheal type 1,4-addition product 6a in 38% yield. The treatment of 2-methylfuran did not alter the reaction pattern, and 1,4-addition product 6b was obtained in a better yield (59%).…”
Section: Entries 2-5)mentioning
confidence: 99%
“…[5] However, recent re- ports show that Pt and Au complexes induce simple allene-dienes I to undergo intramolecular [2 + 2], [4 + 2] and [4 + 3] cycloaddition reactions (Scheme 1). [6] A subsequently performed DFT calculation suggested that both the [4 + 2] and [4 + 3] cycloadditions proceed through an initial gold-catalyzed concerted [4 + 3] cycloaddition of a gold-activated allene with a diene to a carbene intermediate like III. [7] The selectivity for either pathway depends on a preference for either 1,2-H or 1,2-alkyl shifts that the gold-stabilized intermediate III experiences.…”
mentioning
confidence: 99%
“…However with distally monosubstituted allenes like 2 the reactions usually require more stringent conditions and can lead to mixtures of isomers (B and B', Figure 2, box 2). [12,13] Moreover, at the outset, it was not clear how the presence of substituents in the diene or of stereocenters in the connecting tether could influence the efficiency and stereoselectivity of the reaction. [12][13][14] In designing the precursor, and considering that these cycloadditions are proposed to proceed through an exo-like transition state, [12] we envisioned that a bulky group in C4 such as a silyl ether (X = OSiR3), would allow the stereoselective formation of the trans-fused intermediate II, via a transition state like TS-I ( Figure 2, Box 1).…”
mentioning
confidence: 99%
“…[12,13] Moreover, at the outset, it was not clear how the presence of substituents in the diene or of stereocenters in the connecting tether could influence the efficiency and stereoselectivity of the reaction. [12][13][14] In designing the precursor, and considering that these cycloadditions are proposed to proceed through an exo-like transition state, [12] we envisioned that a bulky group in C4 such as a silyl ether (X = OSiR3), would allow the stereoselective formation of the trans-fused intermediate II, via a transition state like TS-I ( Figure 2, Box 1). Hopefully, a selective 1,2-migration of the hydrogen at C7 would allow the exclusive formation of the adduct 3, which would then be submitted to a stereoselective oxygenation.…”
mentioning
confidence: 99%
“…Among unsaturated substrates involved in these transformations, allenes offered an incomparable versatility since they participate in [2+2], [4+2] or [4+3] cyclizations. 2 In contrast, intermolecular gold-catalyzed cycloadditions with allenes have been less studied. 3 In this sense, significant gold-catalyzed intermolecular [2+2] 4 and [4+2] 5 cycloadditions have been recently reported, 6 including examples of enantioselective versions.…”
mentioning
confidence: 99%